2017
DOI: 10.1016/j.neuroimage.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of fronto-parietal beta and theta networks as a signature of visual awareness in neglect

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. In the neglect syndrome, the perceptual deficit for contra-lesional hemi-space is increasingly viewed as a dysfunction of fronto-parietal cortical networks, the disruption of which has been described in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 106 publications
4
16
0
Order By: Relevance
“…Overall, our EEG results converge with previous M/EEG studies reporting electrocortical abnormalities in stroke patients with hemineglect (Colson et al 2001;Demeurisse, Hublet, and Paternot 1998;Yordanova et al 2016) and add novel neurophysiological evidence to support recent findings of neurometabolic (i.e. fMRI) alterations in functional brain networks after stroke .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, our EEG results converge with previous M/EEG studies reporting electrocortical abnormalities in stroke patients with hemineglect (Colson et al 2001;Demeurisse, Hublet, and Paternot 1998;Yordanova et al 2016) and add novel neurophysiological evidence to support recent findings of neurometabolic (i.e. fMRI) alterations in functional brain networks after stroke .…”
Section: Discussionsupporting
confidence: 90%
“…These changes are consistent with non-specific effects of brain lesions on focal delta activity (van Dellen et al 2013), and they did not correlate with neglect symptoms. On the other hand, theta connectivity mainly exhibited a bilateral reduction of long-range intra-hemispheric connections, partially consistent with recent work reporting reductions in fronto-parietal theta and beta coherence in other EEG studies of stroke patients with hemineglect (Fellrath et al 2016;Yordanova et al 2017). However, we found that the theta changes did not correlate with neglect severity either, suggesting that the previously reported changes may constitute non-specific sequels of stroke lesions.…”
Section: The Multiplex Fnc Signature Of Hemineglectsupporting
confidence: 90%
See 1 more Smart Citation
“…Intracranial studies on monkeys performing a visual search attention task showed an active involvement of β oscillatory activity in frontal and parietal regions during top-down attention (Buschman and Miller, 2007 ). Neurological impairments, such as neglect, could cause a reduction of frontal-parietal network strength within the θ and β frequency bands during conscious visual tasks (Yordanova et al, 2017 ), validating the hypothesis of their involvement in both spatial attention and visual processing. On the other hand, increased θ activations in both prefrontal and medial-temporal lobe has been previously shown to positively correlate with successful recall of encoded words (Sederberg et al, 2003 ), with successful decision making regardless of spatial learning (Guitart-Masip et al, 2013 ), and with orchestrating item distinction, verbal working memory and long-term memory (Meyer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 69%
“…In humans, PPC is believed to be involved in the integration of sensory information with motor plans, which is severely impaired in PD patients with FoG [ 48 ]. Indeed, the spatial navigation deficits seen after damage of bilateral PPC as in Balint’s syndrome [ 49 ] or neglect [ 50 ] arise because of the inability to integrate spatial orientation with current/future planning of the voluntary movement needed to accomplish the end goal. If the PPC is in general believed to play such a complicated role, then each hemispheric area has been characterized with specific roles.…”
Section: Discussionmentioning
confidence: 99%